Enhanced electrochemical determination of quercetin in a choline chloride-based ionic liquid. Issue 10 (27th February 2023) - Guo, Meiling; Wang, Zhangxu; Wang, Zixin; Zhang, Lin
Abstract : Au nanoparticles and graphene were used as modified electrodes. A DES was used as an enhancer for quercetin detection. Strong H-bond interactions were formed between the DES and quercetin. Determination in Huang-Qi-Jing oral liquid was achieved. Abstract : Electrochemical techniques have been applied to determine quercetin and to evaluate its antioxidant effect. Deep eutectic solvents as a new generation of green solvents are promising electrolyte catalytically active additives for electrochemical oxidation of quercetin. Herein, in this work, Au was directly electrodeposited on the surface of graphene-modified glassy carbon electrodes, and AuNPs/GR/GC electrodes were fabricated. Choline chloride-based ionic liquids as deep eutectic solvents were readily prepared and applied to detect quercetin in buffer solutions, allowing a detection enhancement. X-ray diffraction and scanning electron microscopy were carried out to characterize the morphology of AuNPs/GR/GCE. Fourier transform infrared spectroscopy was carried out to interpret the H-bond interactions between the DES and quercetin. This electrochemical sensor exhibited good analytical performance. The low detection limit was reduced to 0.5 μM in a 15% DES solution, which was 300% higher than the signal without DES. It proved to be fast and environmentally friendly for the determination of quercetin and the DES had no effect on antioxidant effects of quercetin. In addition, it has been successfully applied in real sample analysis.